The Book of Jerry Falwell : Fundamentalist Language and Politics - Harding, Susan Friend (Book collections on Project MUSE., 2001)
Harding focuses on the words - sermons, speeches, books, audiotapes, and television broadcasts - of individual preachers, particularly Falwell, as they rewrote their Bible-based tradition to include, rather than exclude, intense worldly engagement. As a result of these efforts, born-again Christians recast themselves as a people not separated from but engaged in making history."--Jacket.